Willingness to pay for Agricultural Environmental Safety - Chiara M. Travisi; Peter Nijkamp (Tinbergen Institute, 2004)
The widespread use of pesticides in agriculture provides a particularly complex pattern of multidimensionalnegative side-effects, ranging from food safety related effects to the deterioratian of farmland ecosystems.The assessment of the economic implications of such negative processes is fraught with many uncertainties.This paper presents results of an empirical study recently conducted in the North of Italy aimed at estimatingthe value of reducing the multiple impacts of pesticide use. A statistical technique known as conjoint choiceexperiment is used here in combination with contingent valuation techniques. The experimental design ofchoice modelling provides a natural tool to attach a monetary value to negative environmental effectsassociated with agrochemicals use, In particular, the paper addresses the reduction of farmland biodiversity,groundwater contamination and human intoxicatian. The resulting estimates show that, on average,respondents are prone to accept substantial willingness to pay premia for agricultural goods (in particular,foodstuff) produced in environmentally benign ways.
Keywords: C42; H23; I12; Q24; 330; pesticide risks; food safety; willingness-to-pay; choice modeling; contingent valuation; Lebensmittelsicherheit; Pestizid; Umweltbelastung; Willingness to pay; Landwirtschaft